THE PROBLEMS OF CREATING A HEALTHY PSYCHOLOGICAL ENVIRONMENT IN SOCIETY BULLYING IN EDUCATIONAL INSTITUTIONS THE IMPORTANCE OF LICENSING PSYCHOLOGISTS (American Journal of Interdisciplinary Research and Development, 2024)
The article describes the author's model of psychological service in the educational environment, reveals the main goals and objectives of its work, as well as innovative tools for collecting and analyzing the results.